Testamentary identities: the evidence of selected wills and testaments from the Dioceses of Norwich and Canterbury, 1450-1530 - Marchbank, Alexandra J. (2020)
Historians have long argued over whether the will and testament can be used as accurate evidence of an individual’s life and particularly their religious interests. This project argues for a reconceptualization of these documents, and demonstrates that the will and testament was a document where testators made, rather than just reflected upon, their identities. By comparing the market towns of Faversham (Kent) and Thetford (Norfolk), it specifically questions how the location of production and the gender of the testator shaped the testamentary subject that was produced.